Atelier. - Duborgel, Bruno (Saint-Etienne : La Serre - Ecole des Beaux-Arts de Saint-Etienne, 1987)
Brifflot, Pascale ; Celle, Nathalie ; De Ghellinck, Christophe ; Menart, Sylvie ; Weisbuch, Claude ; Favier, Philippe ; Orsini, Patrick ; Scanreigh, Jean-Marc ; Bajard, Bertrand ; Carruesco, Flora ; Kalfas, Christos ; Claudé, Annick
Atelier, La Serre - Ecole des Beaux-Arts de Saint-Etienne, du mardi 3 février au vendredi 20 février 1987
boek